Inovasi Pembelajaraan Ilmu Pengetahuan Sosial untuk Membangun Karakter dan Keterampilan Abad-21 di Sekolah - Purnama Syapurrohman; Najwa Alya Nastiah; Lulu Rahmawati; Ahmad Ruslan (Syntax Idea)
Social studies learning is a science that considers various social studies disciplines and basic human activities and combines them naturally so as to provide deep insight and understanding to students. Social studies learning in schools currently aims to improve the quality of education and enable social studies to truly gain understanding, critical thinking and problem solving skills in everyday life. Teachers must be able to adapt their learning methods to current developments. Nowadays, not only teachers convey information, but students also participate in the learning process. In the 21st century, information technology continues to develop. Development is increasingly advanced and rapid. The aim of this literature study is to: 1) Find out whether social studies learning at school is related to the skills needed in the 21st century. 2) Identify what skills can be obtained through social studies learning at school. 3) Explain how to learn and apply the development of 21st century skills in social studies learning. The articles analyzed are the results of empirical and conceptual studies. The research results show that the 2006 Curriculum, the 2013 Curriculum, and the Merdeka Curriculum utilize K21 differently in social studies learning. The findings show that studying the social sciences is still relevant for skills development in the 21st century. Skills gained through the study of social sciences include interpersonal skills, collaboration skills, networking skills, and communication skills. In order to effectively incorporate 21st century skills into social studies learning, the learning model needs innovation.